2019
DOI: 10.1039/c9ra05262c
|View full text |Cite
|
Sign up to set email alerts
|

A marine sponge associated fungal metabolite monacolin X suppresses angiogenesis by down regulating VEGFR2 signaling

Abstract: Cancer is one of the leading causes of global deaths and there is an urgent need for the development cancer treatment; targeting VEGFR2 could be one of the promising therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Nagabhishek et al [47] demonstrated the antiangiogenic ability of Monacolin X in vivo, ex vivo, in vitro, and in silico models via downregulation of the VEGFR-2. The compound showed inhibition of in vivo angiogenesis in CAM assay and vascular sprouting in the aortic ring and also showed a reduction of ISVs and SIVs length in transgenic zebrafish embryos Tg (Kdr:EGFP).…”
Section: Monacolin Xmentioning
confidence: 99%
“…Nagabhishek et al [47] demonstrated the antiangiogenic ability of Monacolin X in vivo, ex vivo, in vitro, and in silico models via downregulation of the VEGFR-2. The compound showed inhibition of in vivo angiogenesis in CAM assay and vascular sprouting in the aortic ring and also showed a reduction of ISVs and SIVs length in transgenic zebrafish embryos Tg (Kdr:EGFP).…”
Section: Monacolin Xmentioning
confidence: 99%
“…Graded alcohol was used to dehydrate the slides, followed by xylene (2X, 5 min). After drying, the slides were mounted in toluene and imaged [ 81 , 82 ]. The following antibodies from various vendors were used for the immunohistochemistry study: anti-Ki 67 (Abcam, ab15580); Anti-SOD1 (CST 65778, Boston, MA, USA); Anti-GPX4 (ab125066, Abcam, Boston, MA, USA); Anti-4-Hydroxynonenal (R&D Systems; Biotechne, MAB3249, Minneapolis, MN, USA); Anti-MUC2 (Abcam, ab272692, Boston, MA, USA); Anti-MUC4 (Santa Cruz, SC-33654, Dallas, TX, USA); anti-claudin 1 (Proteintech, 13050-1-AP, Rosemont, IL, USA); anti-occludin (Proteintech, 66378-1-Ig); Anti-F4/80 (Abcam, ab300421, Boston, MA, USA); anti-pIKKβ (CST, 36214SF, Boston, MA, USA); anti-pNF-kB (Abcam, ab131100, Boston, MA, USA); anti-TNF-α (Abcam, ab1793, Boston, MA, USA); Anti-pSTAT3 (CST, 9145, Boston, MA, USA); Anti-CD3 (CST, 78588, Boston, MA, USA); Anti-RORγ (Abcam, ab207082, Boston, MA, USA); Anti-FOXp3 (CST, 12653, Boston, MA, USA); Anti-MPO (Proteintech, 22225-1-AP); Anti-Ppar g (Proteintech, 16643-1-AP, Rosemont, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…KMM 701 targeting two alkaloid binding sites on the molecule [173]; marine sponge Clathria frondifera associated fungus Monascus sp. NMK7-derived polyketide monacolin X (147) that suppressed angiogenesis by downregulation of the VEGFR2 signaling pathway [174]; marine sponge Diacarnus erythraeanus-derived norterpene peroxide (-)-muqubilin A (148) found to be a retinoic acid receptor α positive allosteric modulator and retinoic acid signaling enhancer [175]; marine sponge Mycale aff. nullarosette-derived polyketide mycalolide A (149) that inhibited cytokinesis by disruption of F-actin and binucleation induction [176]; marine blue mussel Mytilus edulis-derived dodecapeptide (150) that promoted growth of osteoblasts, bone loss reduction in ovariectomized mice and interacted with integrins 1L5G and 3V14 [177]; tilapia Oreochromis niloticus-derived oligopeptide (151) shown to be protective of angiotensin II-induced hypertensive endothelial injury by affecting Nrf2 and NF-kB signaling pathways [178]; marine fungus Penicillium sp.…”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%